Analysis of Embryo Transfer Pregnancy Rate from Friesian Holstein Cow Recipients in Bet Cipelang - Syahdan, Roshif; Atabany, Afton; Komala, Iyep; Ningtias, Putri Indah (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
Indonesia has significant potential in the beef and dairy cattle sectors but faces challenges in improving the genetic quality of livestock. Embryo Transfer (ET) is a biotechnological approach that can enhance genetic quality and livestock productivity. This study aims to examine and analyze the factors affecting the success rate of pregnancies in FH dairy cattle as recipients of embryo transfer at Balai Embrio Ternak (BET) Cipelang. Secondary data from BET Cipelang (2017-2023) were used, including variables such as embryo quality, transfer methods, recipient age, estrus synchronization methods, and embryo donor breeds. The results showed that good embryo quality (24.55%) and fresh transfer methods (35.19%) significantly increased pregnancy success (p 0.05). Synchronization methods using PGF2 and a combination of Progesterone + PGF2 increased the chances of pregnancy by 3.60 and 3.89 times, respectively, compared to natural estrus. Although not statistically significant, recipient age groups of 3-5 years and 6-9 years had higher pregnancy success rates compared to the 10-12 years age group. The donor breed of embryos did not show a significant effect on pregnancy rates. Therefore, this study concludes that good embryo quality and fresh transfer methods significantly increase the pregnancy success rate in FH dairy cattle at BET Cipelang. The factors influencing pregnancy rates include embryo quality, transfer methods, recipient age, estrus synchronization methods, and donor breed, with embryo quality and fresh transfer methods having the greatest impact. To improve pregnancy rates, it is recommended to select high-quality embryos, use fresh transfer methods, and implement effective estrus synchronization protocols, such as PGF2 injection or a combination of Progesterone + PGF2. Further research involving various recipient cattle breeds and genetic and environmental factors is also advised.